Molybdenum-induced effects on photosynthetic efficacy of winter wheat (Triticum aestivum L.) under different nitrogen sources are associated with nitrogen assimilation - Imran, Muhammad (Plant physiology and biochemistry : PPB, 2019)
Copyright © 2019 Elsevier Masson SAS. All rights reserved.